2009
DOI: 10.1111/j.1365-4632.2009.03998.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes and lipid peroxidation at the tissue level in patients with stable and active vitiligo

Abstract: Our study shows that oxidative stress is involved in the pathophysiology of both active and stable vitiligo, but an increased imbalance of antioxidants is observed in the tissues of patients with active vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 18 publications
3
58
0
2
Order By: Relevance
“…Our results suggested that erythrocyte MDA levels were not altered in vitiligo patients regardless of disease activity. Previous studies have shown higher MDA levels in both serum and tissues in vitiligo patients compared to healthy controls 3,4,6,[8][9][10]15 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our results suggested that erythrocyte MDA levels were not altered in vitiligo patients regardless of disease activity. Previous studies have shown higher MDA levels in both serum and tissues in vitiligo patients compared to healthy controls 3,4,6,[8][9][10]15 .…”
Section: Discussionmentioning
confidence: 88%
“…The etiology of vitiligo remains unclear, but oxidative stress and the accumulation of free radicals have been proposed as important pathogenic mechanisms [3][4][5] . Increased malondialdehyde (MDA) levels are reported in the skin of patients with active vitiligo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that individuals with vitiligo have a compromised antioxidant response, [43] with enzymes such as catalase and superoxide dismutase present at higher than expected levels in tissue from perilesional areas and in sera from patients with vitiligo. [44] Melanocytes in perilesional sites of vitiligo patients display hallmark dilation of the ER. [45] The ER is a sensor of cellular stress.…”
Section: Aetiologymentioning
confidence: 99%
“…The biochemical theory ascribes the destruction of melanocytes to autocytotoxic metabolites, which derive from the synthesis of melanin. Several studies prove the presence of oxidative stress and the accumulation of free radicals in the epidermal layer of affected skin, and recently antioxidant enzymes and lipid peroxidation have been detected in the tissues of vitiligo patients [2,4]. Le Poole et al in 1993 worked out the ''convergence theory'', which suggests the synergistic role of all the above-mentioned factors and cells in the pathogenesis of vitiligo [9].…”
Section: Introductionmentioning
confidence: 99%